PGK1 is a Potential Survival Biomarker and Invasion Promoter by Regulating the HIF-1α–Mediated Epithelial-Mesenchymal Transition Process in Breast Cancer - Fu, Deyuan; He, Chunlan; Wei, Jinli; Zhang, Zhengquan; Luo, Yulin; Tan, Haosheng; Ren, Chuanli (Cellular physiology and biochemistry, 2018)
Background/Aims: Glycolysis, a multi-step enzymatic reaction, is considered to be the root of cancer development and progression. The aim of this study is to figure out which glycolysis enzyme participates in the progression of breast cancer and its possible mechanisms. Materials: We firstly screened out PGK1 by performing an RT-PCR array of glycolysis-related genes in three paired breast cancer samples, and further investigated PGK1 using TCGA and our own database. The effect and mechanism of PGK1 on cell invasion was further explored both in vitro and using patient samples. Results: PGK1 was most upregulated in T3N0 with distant metastases compared to those with no metastases. In the TCGA database, high PGK1 expression predicted poor overall survival (OS) in breast cancer and some other cancers (P< 0.001). In the validation cohort, high PGK1 expression was significantly correlated with larger tumor size (P=0.011) and advanced TNM stage (P=0.033), and PGK1 expression was an independent prognostic factor for OS and disease free survival (DFS) in both univariate and multivariate regression analyses (P< 0.05). Functional studies indicated that knockdown of PGK1 expression significantly inhibited invasion and reversed the epithelial-mesenchymal transition process in breast cancer cells (P< 0.05). Mechanistically, PGK1 increased HRE luciferase activity in a dose-dependent manner, while silencing PGK1 expression decreased HRE activity. Conclusion: High PGK1 expression was associated with poor prognosis in breast cancer, because PGK1 and HIF-1α formed a positive feed-forward loop and thus stimulated breast cancer progression and metastases. Based on these results, PGK1 may serve as a promising biomarker and target therapy for breast cancer.